Estimating the effects of shrinking the criminal justice system on criminal recidivism - Loeffler, Charles E. (Criminology & public policy, 2022)
Research Summary We examined the impact of Raise the Age (RTA) in Massachusetts, which increased the maximum jurisdictional age for its juvenile court in late 2013. Using statewide re-arraignment data and a difference-in-differences research design comparing affected 17-year-olds to unaffected 18-year-olds, we find that RTA increased recidivism for affected 17-year-olds. The observed increases in recidivism were especially large for 17-year-olds without prior justice involvement. This result may stem from the more extensive use of pretrial supervision or the diminished deterrence of prosecution within the Massachusetts juvenile justice system. Policy Implications This study demonstrates that prosecuting older adolescents as juveniles can exacerbate rather than reduce future justice involvement. This finding highlights the ongoing risk of unanticipated and iatrogenic impacts of criminal justice interventions. It also suggests the need for caution in further expansions of RTA until evidence of anticipated programmatic benefits can be confirmed.